2018
DOI: 10.7224/1537-2073.2016-021
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Behavior and Blood Pressure in Patients with Multiple Sclerosis

Abstract: Background: Sedentary behavior is a pervasive public health concern in the general population. To date, little is known regarding the possible health risks associated with sedentary behavior in patients with multiple sclerosis (MS), although this population has increased risks of comorbidities such as hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Other common co-morbidities associated with MS like hypertension and diabetes could be related unhealthy lifestyle. This finding supported by [54,55] who reported that hypertension is one co-morbid condition that affects 10% to 30 % of MS patients and increases with age. While [56] mentioned that some autoimmune diseases like MS, associated with certain genotypes that increased risk of damage of islet beta cells and may lead to occurrence of diabetes.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Other common co-morbidities associated with MS like hypertension and diabetes could be related unhealthy lifestyle. This finding supported by [54,55] who reported that hypertension is one co-morbid condition that affects 10% to 30 % of MS patients and increases with age. While [56] mentioned that some autoimmune diseases like MS, associated with certain genotypes that increased risk of damage of islet beta cells and may lead to occurrence of diabetes.…”
Section: Discussionsupporting
confidence: 83%
“…It can cause; extensive physical disabilities, delay MS diagnosis, increase hospitalization, increase the chance of death or lack of effective treatment and negative impact quality of life. [54] confirmed that hypertension is consider as one of the main top five leading causes of disability among MS patients as a result of sedentary life behavior. While [60] reported that co-morbid medical conditions such as diabetes can substantially affect neurologic disease such as MS outcomes, higher blood glucose concentration is associated with poorer self management outcomes and this due to reduced mobility and sedentary lifestyle.…”
Section: Discussionmentioning
confidence: 79%
“… 3 7 In MS, we are aware of one study linking sitting time with blood pressure. 11 Comorbidities could accelerate disease progression 9 and result in a vicious cycle among manifestations of MS, SB, comorbidity, and disease progression. Whereas studies examining those associations are necessary to establish if SB has deleterious effects in patients with MS, a current priority is to determine the prevalence of this behavior in MS.…”
Section: Introductionmentioning
confidence: 99%
“…Among the general population, sedentary behaviour has adverse effects on health such as increased cardiometabolic risk,19 depression,20 type 2 diabetes21 and mortality,22 23 even in those who are physically active. Recent work with persons with MS shows that sedentary behaviour is related to blood pressure 24. In addition to the health benefits of sitting less, research with older adults and those with disability shows that less sitting, and especially more breaks from sitting, is positively associated with less frailty25 and better mobility 26.…”
Section: Introductionmentioning
confidence: 99%